Strength-Based School Counseling in Addressing School Bullying Issue in Indonesia - Ein, Indy Hurun; Idriyani, Natris (Jurnal Kajian Bimbingan dan Konseling, 2024)
As the school bullying issues rates have been increasing in the past decade, further comprehesinve actions from professionals in educarion are needed, mainly from school counselors. This paper aims to provide information and highlight key principles of strengths-based school counseling approach that would be compatible to deal with the issues. Using this contemporary approach, school counselors are highly recommended to work with other school stakeholders to create a positive environment and climate for students to prevent them from being both bullies and victims, including actions to identify students’ positive qualities, assign parents to enhance positive communications and relationships with their children, establish appropriate classroom guidance, and involve related communities in specific decision making regarding students’ needs and development.